Anticardiolipin Antibody Assay: a Methodological Analysis for a better Consensus in Routine Determinations - Tincani, Angela; Allegri, Flavio; Sanmarco, Marielle; Cinquini, Massimo; Taglietti, Marco; Balestrieri, Genesio; Koike, Takao; Ichikawa, Kenji; Meroni, Pierluigi; Boffa, Marie Claire (Thrombosis and Haemostasis, 2001)
Despite the widely recognized practical importance of anticardiolipin (aCL) ELISA, the reliability of this test has been recently discussed. In order to investigate this area on European scale, we sent to 30 experienced centers a questionnaire focusing on the diagnostic procedures applied to patients with antiphospholipid syndrome (APS) and on the detailed protocols used to perform aCL. Anticardiolipin ELISA was found to be the most frequently performed test in patients with suspected APS, but significant difference was shown among the various protocols. The cross-laboratory multiple examination of ten serum samples evaluated independently by the 24 centers pointed out the difficulty in getting comparable results. Therefore a “consensus” protocol was derived from the aCL methods giving the best performance. The materials and reagents necessary to perform the “consensus” method, including, as putative standards, one IgG and one IgM monoclonal antibody (HCAL and EY2C9) were distributed to 19 Centers. The results of one IgG and one IgM aCL high positive sera measured in serial dilutions were compared. A progressive decrease in the variability of the values obtained for a given sample appeared evident when all the laboratories used the same standard, in their own in-house ELISA and even more in the “consensus” ELISA.Our data show that aCL ELISA standardization is necessary in order to obtain comparable results in different laboratories.
Keywords: Antiphospholipid syndrome; anticardiolipin antibodies; standardization